American Sign Language & Emergency Alerts: The Relationship between Language, Disability, and Accessible Emergency Messaging. Issue 1 (March 2018) - Bennett, DeeDee; LaForce, Salimah; Touzet, Christina; Chiodo, Kay
Emergency alert messages are not always completely accessible for people who are Deaf that rely on American Sign Language (ASL). ASL is a visual and conceptual language that has its own unique syntax and grammar. ASL has no roots in English and is the 3 rd most taught foreign language in our colleges today. Not all individuals who are deaf rely on ASL for "clear and effective" communication. For many individuals who become hard-of-hearing or deaf later in life (late-deafened), closed captioning can provide accommodations. For individuals who are Deaf and rely on ASL as their primary language, closed captioning is not a useful means of communication because the information is being conveyed in a language most ASL users do not fully comprehend. Similarly, emergency alert messages delivered via SMS text or email can also present confusion to ASL users who may struggle to understand the written English messages. One size does not fit all; and in this case, English text as a sole means of communication is not entirely accessible for people who rely on ASL. This paper outlines the relationship between language, disability, and emergency messaging as learned from several research studies examining the accessibility of public alerts and warnings.